Climate Change: Effects on Biodiversity and Ecosystem Functioning - Werner, Florian; Jantz, Nele; Krashevska, Valentyna; Peters, Thorsten; Behling, Hermann; Maraun, Mark; Scheu, Stefan; Brehm, Gunnar (Ecosystem services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador. Ecological Studies, 2013)
Understanding the resistance of plant and decomposer communities to climate change is critical for predicting the future of tropical biodiversity and ecosystem functioning. In this chapter we present data from three independent field studies related to climate change effects in the moist Andes of Southeast Ecuador. Pollen records suggest that large climatic fluctuations during the late Pleistocene and Holocene affected the unusually low forest line of southern Ecuador in ways that were expected, with warming trends resulting in an elevation of the timber line. However, our analysis of present-day tree assemblages at ten forest line sites suggests that the regional timberline is not primarily determined by temperature, and that rising temperature alone is hence unlikely to cause a pronounced upshift of the region’s forest line. Experimental rain exclusion strongly reduced the density, but not the species richness, of testate amoebae irrespective of altitude (1,000–3,000 m), suggesting that increasing drought occurrence may affect nutrient mineralization in the future.
UnivIS-Import:2015-04-20:Pub.2012.nat.dgeo.IG.zentr.climat